Managing Workplace Stress The Cognitive Behavioural Way - Choudhury, Koushiki; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
This book is focussed at those who are working or are about to enter the workplace. According to the book, workplace may be defined as "any environment enabling work to be done". This broader definition will make the workplace include any situation or place where people interact to exchange knowledge and information. The book discusses the various anxiety and stress inducing events that one faces in the workplace and the ways to cope with them, using Rational Emotive Behaviour Therapy (REBT), and Cognitive Therapy (CT). These techniques are the most widely used psychotherapeutic techniques and their effectiveness has been tested scientifically throughout the world. The book attempts to show as to how Cognitive Behaviour Therapy (umbrella term for CT and REBT) can be used to challenge and overcome workplace stress issues such as criticism, abuse, animosity, conflicts, disagreements, insubordination, organisational politics, favouritism, prejudices, discriminations, job uncertainties, extreme work pressures, excessive workloads, poor job designs, job mismatches, role conflicts, role ambiguities, cultural and ethical maladjustments, workplace boredom and anger problems by realistically and accurately interpreting events at the workplace. It includes plenty of real-life stress producing scenarios as examples and specific techniques to challenge them. Moreover, it tries to analyze and solve workplace stress issues in a very lucid, simple and direct manner so that it appeals to and is understood by a wide range of people. The book is based on research and studies in the area of internal marketing, psychological counselling and workplace stress, and is the product of years of surveys and professional interactions in the industry and the academia.
1.Workplace Stress -- 2.What is Rational Emotive Behaviour Therapy -- 3.Rational and Irrational Beliefs -- 4.The ABC Framework -- 5.Cognitive Errors -- 6.Rational Emotive Behaviour Therapy in the Workplace -- 7.Cognitive Behaviour Therapy.
Keywords: Economics; Quality of Life; Quality of Life -- Research; Applied psychology; Economics/Management Science; Human Resource Management; Psychotherapy and Counseling; Quality of Life Research; Industrial and Organisational Psychology